Antigenic Site-Specific Competitive Antibody Responses to the Fusion Protein of Respiratory Syncytial Virus Were Associated With Viral Clearance in Hematopoietic Cell Transplantation Adults - Ye, Xunyan; Iwuchukwu, Obinna P.; Avadhanula, Vasanthi; Aideyan, Letisha O.; McBride, Trevor J.; Ferlic-Stark, Laura L.; Patel, Kirtida D.; Piedra, Felipe-Andres; Shah, Dimpy P.; Chemaly, Roy F.; Piedra, Pedro A. (Frontiers in Immunology, 2019)
Background. Recent studies of human sera showed that the majority of the respiratory syncytial virus (RSV) neutralizing antibodies are directed against pre-fusion conformation of the fusion (F) protein of RSV and revealed the importance of pre-fusion antigenic site Ø specific antibodies. However, detailed analysis of multiple antigenic site-specific competitive antibody responses to RSV F protein and their contribution to virus clearance in humans are lacking. Methods. We prospectively enrolled a cohort of RSV infected hematopoietic cell transplantation (HCT) adults (n=40). Serum samples were collected at enrollment (acute, n=40) and 14 to 60 days post-enrollment (convalescent, n=40). Antigenic site-specific F protein antibodies were measured against pre-fusion site Ø, post-fusion site I, and sites II and IV present in both the pre-fusion and post-fusion F protein conformations utilizing four different competitive antibody assays developed with biotinylated monoclonal antibodies (mAb) D25, 131-2A, palivizumab, and 101F, respectively. The lower limit of detection were 7.8 μg/mL and 1.0 μg/mL for the competitive antibody assays that measured site Ø specific response, as well as sites I, II and IV specific responses, respectively. Neutralizing antibody titers to RSV A and B subgroups was determined by microneutralization assays. Results. The overall findings in RSV infected HCT adults revealed: 1) a significant increase in antigenic site-specific competitive antibodies in convalescent sera except for site Ø competitive antibody (p<0.01); 2) comparable concentrations in the acute and convalescent serum samples of antigenic site-specific competitive antibodies between RSV/A and RSV/B infected HCT adults (p>0.05); 3) significantly increased concentrations of the antigenic site-specific competitive antibodies in HCT adults who had genomic RSV detected in the upper respiratory tract for <14 days compared to those for ≥14 days (p<0.01); and 4) statistically significant correlation between the antigenic site-specific competitive antibody concentrations and neutralizing antibody titers against RSV/A and RSV/B. Conclusions. In RSV infected HCT adults, antigenic site-specific antibody responses were induced against multiple antigenic sites found in both the pre-fusion and post-fusion F conformations, and were associated with a more rapid viral clearance and neutralizing antibody activity. However, the association is not necessarily the cause and the consequence.